Tamaños y proporción sexual de Ucides occidentalis (Crustacea: Gecarcinidae) en un manglar de Costa Rica - Vives Jiménez, Fernando (1995)
Sizes and sex ratios of Ucides occidentalis (ORT-MANN 1897) were studied in the mangrove area of Estero Panama, Guanacaste, Costa Rica, from March to August 1982. The caparace length was 36.7-84.5 mm for males and 36.00-60.8 mm for females. The mean sex-ratio was 1.96±1.30 males per female. The relationship between caparace length and weight were W=1.17 x 10-2 Lc2,3970 for males and W=2.38 x 10-3 Lc2,7354 for females. The relative growth was allometric for the length-weight relationships in both sexes.